Bringing Giftedness to Bear: Generativity, Meaningfulness, and Self-Control as Resources for a Happy Life Among Gifted Adults - Vötter, Bernadette; Schnell, Tatjana (Frontiers in Psychology, 2019)
Meaning in life has been found to be of particular importance for the subjective well-being of intellectually gifted individuals. However, there is a lack of research about what contributes to gifted adults’ meaning in life and how it could be enhanced. This study examined if the devotion of one’s gift or talent to the well-being of others—i.e., the source of meaning “generativity”—would lead to a sense of meaning and, in further consequence, result in higher subjective well-being over time. Furthermore, we hypothesized that the effect of meaningfulness on subjective well-being was conditional on trait self-control. Longitudinal data of two gifted groups was obtained via an online study: 100 intellectually gifted individuals (55% female; mean age 43 ± 9 years) and 52 high academic achievers (29% female; mean age 57 ± 14 years). The former group experienced significantly lower levels of meaningfulness (p = 0.001, 2 = .076), self-control (p < 0.001, 2 = .090), and generativity (p = 0.025, 2 = .034) than the latter. As expected, the actualization of generative orientations in life enhanced both gifted groups’ meaningfulness and, in further consequence, their subjective well-being over time. Furthermore, the positive association between life meaning and subjective well-being was enhanced by trait self-control among the intellectually gifted but not among the high academic achievers. However, as proposed, the latter’s subjective well-being was strongly related to self-control. Results highlight that a generative orientation can help gifted individuals to advance a personal sense of meaning and happiness over time. In this context, intellectually gifted individuals appear to particularly benefit from self-control. Consequently, the intrinsic willpower to subdue inner responses, emotions as well as undesired behaviors might strengthen the positive effect between sources of meaning, life meaning, and subjective well-being.